Forest Pathology and Entomology - Moricca, Salvatore; Panzavolta, Tiziana (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The 22 papers that make up this Special Issue deal with pathogen and pest impact on forest health, from the diagnosis to the surveillance of causative agents, from the study of parasites' biological, epidemiological, and ecological traits to their correct taxonomy and classification, and from disease and pest monitoring to sustainable control strategies.